Ethical reviews for refinement studies: A case study from Titukulane in Malawi - Babu, Suresh Chandra; Malunga, Anthony; Ranaivoarivelo, Nivo; Patterson, Andrew (CARE Malawi, 2021)
Human rights violation while researching human participants, especially in the biomedical field, and later in social and behavioral science has mandated ethical review of research. Simultaneously, digital privacy breeches and sharing of biometric data is a widespread problem. This has led to the establishment of Institutional Review Boards or similar Ethical Review Boards, which have a significant role in protecting the rights of human participants by holding the researcher accountable. So, in this learning note, we will examine the need, standards, and process of ethical review, particularly for refinement studies, by using the refinement phase of the USIAD funded Titukulane Development Food Security Activity. Using this case study, we will also explain the process Titukulane used to choose which studies needed to be approved by the Institutional Review Board and which did not.